On the existence of solutions of a three steps crisis integro-differential equation - Dumitru Baleanu; Khadijeh Ghafarnezhad; Shahram Rezapour; Mehdi Shabibi (Advances in Difference Equations, 2018)
Abstract There are many natural phenomena including a crisis (such as a spate or contest) which could be described in three steps. We investigate the existence of solutions for a three step crisis integro-differential equation. We suppose that the second step is a point-wise defined singular fractional differential equation.